2007
DOI: 10.1111/j.1750-3639.2007.00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cell Migration into the Central Nervous System: A Few New Twists on an Old Tale

Abstract: Understanding the mechanisms of leukocyte trafficking into the brain might provide insights into how to modulate pathologic immune responses or enhance host protective mechanisms in neuroinflammatory diseases such as multiple sclerosis. This review summarized our knowledge about the sites for leukocyte entry into the central nervous system, highlighting the routes from blood into the perivascular space and brain parenchyma through the blood-brain barrier. We further discussed the multistep paradigm of leukocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
183
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(188 citation statements)
references
References 118 publications
3
183
0
2
Order By: Relevance
“…Histopathological analysis of brain and cervical spinal cord initially indicated similar levels of perivascular infiltrate in both the acute and recovery phases of the disease, even though decreased inflammatory infiltration during the remission phase was expected. We expected a decrease in the level of inflammatory infiltration during the remission phase because established data have shown that inflammatory cells strongly contribute to the pathology of this disease (Man et al 2007). In addition, experimental therapeutic strategies have demonstrated a clear correlation between clinical remission and the prevention of mononuclear cell transmigration to the spinal cord (Stanislaus et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological analysis of brain and cervical spinal cord initially indicated similar levels of perivascular infiltrate in both the acute and recovery phases of the disease, even though decreased inflammatory infiltration during the remission phase was expected. We expected a decrease in the level of inflammatory infiltration during the remission phase because established data have shown that inflammatory cells strongly contribute to the pathology of this disease (Man et al 2007). In addition, experimental therapeutic strategies have demonstrated a clear correlation between clinical remission and the prevention of mononuclear cell transmigration to the spinal cord (Stanislaus et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Various EAE animal studies suggest that the disease severity is correlated with alterations of BBB integrity, and a reduction in the degree of EAE can be achieved by preventing BBB alterations (Fabis et al, 2007). During the course of EAE, autoaggressive CD4 þ T lymphocytes are activated outside the CNS, and can accumulate in the brain and spinal cord by crossing the BBB and BSCB (Ransohoff et al, 2003;Engelhardt et al, 2005;Man et al, 2007). The transport of different subsets of cytotoxic T lymphocytes from the blood to the brain and spinal cord is critical for lymphocytic infiltration of the CNS, which in turn results in neuronal death.…”
Section: Discussionmentioning
confidence: 99%
“…After release from the bone marrow (or spleen), leukocyte transmigration from blood to spinal cord is dependent on a cadre of adhesion molecules and chemokines [73][74][75]. Details of the cellular and molecular characteristics of the multi-step paradigm for leukocyteendothelial interactions at the blood-brain barrier have been published elsewhere [73][74][75].…”
Section: Mechanisms Regulating Intraspinal Accumulation Of Myeloid Cementioning
confidence: 99%
“…Details of the cellular and molecular characteristics of the multi-step paradigm for leukocyteendothelial interactions at the blood-brain barrier have been published elsewhere [73][74][75]. A more comprehensive review of how the complex interplay between neurons and glia regulates the onset of neuroinflammatory cascades after SCI, including the recruitment of neutrophils and monocytes, can be found in recent reviews from our laboratory [3,5].…”
Section: Mechanisms Regulating Intraspinal Accumulation Of Myeloid Cementioning
confidence: 99%